Efek Bubuk Susu Kedelai terhadap Kadar Kolesterol LDL dan HDL Serum Wanita Perimenopause dengan Hiperkolesterolemia - Retno Kuntarti; Sri Sukmaniah; Sri Widia A. Jusman (Lembaga Penelitian Universitas YARSI, 2017)
Perimenopausal women is at risk of atherosclerosis as a result of the increase of LDL cholesterol level and the decrease of HDL cholesterol level. Soy milk powder consumption may protect toward these risk factors. This purpose of study is to investigate the effects of 2x30 g/d soy milk flour for eight weeks on serum cholesterol LDL and HDL levels in hypercholesterolemic perimenopausal women. The 19 subjects received 2x30 g/d soy milk powder for eight weeks. LDL and HDL serum cholesterol levels were determined at 0, 4, 9 weeks. Dietary intakes were assesed using 1x24 hours food recall. Statistical analysis used t Test. After eight weeks intervention, Soy milk powder decreases significant (p less than 0.05) LDL cholesterol levels at the 4th week (8.59 plus-minus 17.31%), and the8th week (7.81 plus-minus 11.32%). Soy milk powder can’t increase HDL cholesterol levels at the 4th and 8th weeks significantly. Soy milk decrease significant the ratio of LDL to HDL (7,03 plus-minus 16,82%) at the 4th week. Consuming soy milk powder 2 x 30 g/d during eight weeks can reduce the LDL cholesterol level and LDL/HDL ratio significantly.